2019
DOI: 10.1021/acs.macromol.9b00753
|View full text |Cite
|
Sign up to set email alerts
|

A Multiscale Model for Solute Diffusion in Hydrogels

Abstract: The number of biomedical applications of hydrogels is increasing rapidly on account of their unique physical, structural, and mechanical properties. The utility of hydrogels as drug delivery systems or tissue engineering scaffolds critically depends on the control of diffusion of solutes through the hydrogel matrix. Predicting or even modeling this diffusion is challenging due to the complex structure of hydrogels. Currently, the diffusivity of solutes in hydrogels is typically modeled by one of three main the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
158
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 162 publications
(179 citation statements)
references
References 55 publications
10
158
1
Order By: Relevance
“…The diffusivity of cargo in PBS was calculated using the Stokes–Einstein law equation for diffusion 71 where k B is Boltzmann’s constant, T is temperature in Kelvin, η is solvent viscosity, and R is the solute hydrodynamic radius The diffusivity of cargo in a model covalent PEG gel was calculated using the multiscale diffusion model (MSDM) assuming 25 °C, a 5% volume fraction, and 35 nm mesh size. 72 The calculated values are comparable to experiment diffusivities of similar sized cargoes found in the literature. 73 …”
Section: Materials and Methodssupporting
confidence: 86%
“…The diffusivity of cargo in PBS was calculated using the Stokes–Einstein law equation for diffusion 71 where k B is Boltzmann’s constant, T is temperature in Kelvin, η is solvent viscosity, and R is the solute hydrodynamic radius The diffusivity of cargo in a model covalent PEG gel was calculated using the multiscale diffusion model (MSDM) assuming 25 °C, a 5% volume fraction, and 35 nm mesh size. 72 The calculated values are comparable to experiment diffusivities of similar sized cargoes found in the literature. 73 …”
Section: Materials and Methodssupporting
confidence: 86%
“…For instance, previous studies have correlated the mechanical properties of hydrogel scaffolds to the differentiation of stem cells into neurons 30 . Yet, the mesh size is often overlooked, even if it is known to be a main contributor to the diffusion properties of solutes in hydrogels 31 . It will undoubtedly be essential for biomaterials to imitate the transport of oxygen, nutrients, and therapeutics in real brain tissue.…”
Section: Mechanical Mismatchmentioning
confidence: 99%
“…1 is the mesh size ( ). Studies on biopolymer solutions and hydrogels have demonstrated that particles of size much smaller than the average mesh size diffuse freely through the meshwork (Axpe et al, 2019;Cai et al, 2011;Carn et al, 2012;Wong et al, 2004). When the probe size is close to the average mesh size, the dynamics of the probes becomes impacted by the polymer mesh.…”
Section: Apparent Average Nucleoid Mesh Size In E Coli Cellsmentioning
confidence: 99%